PENGARUH KEPEMILIKAN INSTITUSIONAL DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Lestari, Lestari (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
This study is aimed to examine the effect of institutional ownership and capital structure on the company’s value. The population used in this study are all manufacturing companies listed in Indonesia Stock Exchange from 2010 until 2014. The main data used in this research is the financial data in 2010 until 2014. Completed and selected financial data this research are 32 companies so that the samples in this research using five periods are 160. For examining data, this research uses panel data regression model. After running chow test and Hausman test, the most suitable method for the regression is fixed effects method. This research shows that institutional ownership has positive influence significantly on the company’s value, capital structure has no influence significantly on the company’s value Keywords: institutional ownership, capital structure, the company’s value